The application of the subsidiary principle for patients’ empowerment for health care: the case of rare diseases in Argentina - Moya, Graciela (Acta Bioethica, 2012)
The subsidiary principle, broadly defined in political and social philosophy, refers not only to the relations between communities, but also to relations of the individual with any type of social community. The subsidiary principle promotes the dignity of persons as social and individual beings by participating and it recognizes as primary the well being of the individual person. According to this principle, individuals or main communities adopt an attitude of help –support, promotion and respect- with respect to minor ones. Adapted, it can be used as parameter to understand the concept of patients’ empowerment for health care. In order to establish this process it is required, on one hand, a physician-patient relationship center in the patient and his/her family, in which they will receive the necessary tools for health care decisions and, on the other hand, the creation of intermediate social entities in which patients and their families may develop strategies for health care enhancement. The goal of this study is to reflect on this principle and to offer a bioethical framework to facilitate understanding and development of the concept of empowerment for health care.